Impact of Environmental Cost on the Performance of Firms in Nigeria (Acta Universitatis Danubius. Œconomica, 2025)
The study investigated the impact of the cost associated to the environmental and market performance of listed companies that explore, refine, produce and distribute oil and gas in Nigeria from 2006 to 2022. The research used a panel least squares regression technique. The study also assessed the environmental costs using Pollution control costs, Penalty costs and Donations and charitable contributions. The study found that there is a weak and non-sufficient relationship between donations and charitable contributions and earnings per share, a strong and significant negative correlation between penalty costs and earnings per share, and a weak and non-sufficient positive relationship between pollution control costs and earnings per share of listed companies that explore, refine, produce and distribute oil and gas in Nigeria. The study suggests that Nigerian enterprises should deliberately allocate resources to improve their environment and adopt environmentally-friendly practices. This not only helps in achieving the widely known goals of environmental sustainability but also positively impacts the firm’s market performance.